The impact of traditional mind–body exercises on pulmonary function, exercise capacity, and quality of life in patients with chronic obstructive pulmonary disease: a systematic review and meta-analysis of randomized controlled trials - Sujie, Mao; Kaiwen, Xiao; Hong, Xu; Xiujin, Guo (Frontiers in Medicine, 2024)
Background Chronic Obstructive Pulmonary Disease (COPD) is a chronic condition characterized primarily by airflow obstruction, significantly impacting patients’ quality of life. Traditional mind–body exercises, as a non-pharmacological intervention for COPD, have become a new research focus. Objective To assess the impact of traditional mind–body exercises (Tai Chi, Qigong, Yoga) on pulmonary function, exercise capacity, and quality of life in COPD patients. Additionally, to identify the most suitable form of traditional mind–body exercise for different indicators. Methods Searches were conducted in databases such as Web of Science, PubMed, EBSCOhost, CNKI, etc., to collect randomized controlled trials (RCTs) evaluating the intervention of traditional mind–body exercises (Tai Chi, Yoga, Qigong) in COPD. The Cochrane evaluation tool was applied for methodological quality assessment of the included literature. Statistical analysis and sensitivity analysis were performed using Revman 5.4 software, while publication bias was assessed using R software. Results This study included 23 studies with a total of 1862 participants. Traditional mind–body exercises improved patients’ FEV1% index (WMD = 4.61, 95%CI [2.99, 6.23]), 6-min walk distance (SMD = 0.83, 95%CI [0.55, 1.11]), and reduced patients’ SGRQ score (SMD = −0.79, 95%CI [−1.20, −0.38]) and CAT score (SMD = −0.79, 95%CI [−1.20, −0.38]). Qigong showed the most significant improvement in FEV1% and 6MWT, while Tai Chi primarily improved 6MWT, and the effect of Yoga was not significant. Sensitivity analysis indicated stable and reliable research conclusions. Conclusion Traditional mind–body exercises are effective rehabilitation methods for COPD patients, significantly improving pulmonary function, exercise capacity, and quality of life. They are suitable as complementary interventions for standard COPD treatment. Systematic review registration [https://www.crd.york.ac.uk/prospero/display-record.php?ID=CRD42023495104], identifier [CRD42023495104].